Research Progress on Mechanical Characteristics of Vertical Cylinders under Internal Solitary Waves - XU Ming; WANG Yin; LING Ming; HU Kelong; XIONG Xiahui; PENG Daosong; XU Jinyao; JI Yong (Renmin Zhujiang)
Internal solitary waves represent a common physical phenomenon in water bodies such as oceans,coasts,and estuaries.They are induced by external disturbances on a pycnocline in a stably stratified water body,and the shear flow excited during their propagation is accompanied by huge energy,which poses a serious threat to the safety and stability of underwater engineering structures.Therefore,it is of great significance to explore the laws of interaction between internal solitary waves and engineering structures.On the basis of summarizing the research progress of many scholars both at home and abroad,the common methods for studies on the action characteristics of internal solitary waves on structures are introduced from the aspects of physical experiments and numerical simulations.In addition,this study gives a summary of the research results in the characteristics and laws of the horizontal force,vertical force,and moment on vertical cylinders under internal solitary waves and the sensitivity factors of the horizontal force.Finally,the issues that require further attention in follow-up research on mechanical characteristics of vertical columns umder internal solitary waves are raised.